Traveling Waves in a Diffusive Predator-Prey Model Incorporating a Prey Refuge - Xiujuan Wu; Yong Luo; Yizheng Hu (Abstract and Applied Analysis)
We establish the existence of traveling wave solutions and small amplitude traveling wave train solutions for a reaction-diffusion system based on a predator-prey model incorporating a prey refuge. By using the shooting argument, invariant manifold theory, and the Hopf bifurcation theorem, we analyze the dynamic behavior of this model in the three-dimensional phase space. Numerical results are also presented to illustrate the theoretical results.